Onestep Footwear Public relations Campaign Planning as an Eco-Friendly Brand - Nur Yasmin Sulma; Yunita Permatasari Simatupang; Andita Putri Bethari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to find out how to plan a public relations campaign to increase public awareness of shoe sole waste. Problems are focused on the degree of excess, disadvantages, opportunities and threats over shoe sole litter. In order to approach this problem, theoretical references from persuasive communication, public relations, campaigns and environmentally friendly products are used. The data was collected through input from the SWOT matrix in the form of questionnaire results that had been filled out by Onestep Footwear and analyzed qualitatively.  This study concluded that overall, the shoe campaign for Bumi collaborated with one of the local shoe Brands from Bandung called Onestep Footwear. With this campaign, it is hoped that there will be an increase in public awareness of environmental pollution caused by shoe sole waste, and the emergence of a sense to continue to protect the environment by using environmentally friendly shoes, such as Onestep Footwear.